Efek Pemberian Minyak Buah Merah pada Penurunan Parasitemia pada Mencit yang Diinfeksi dengan Plasmodium berghei - Elma Sandya Putri; Jhons Fatriyadi Suwandi; Hanna Mutiara; Asep Sukohar (Majority, 2021)
Malaria is one of the endemic infectious disease cases in several areas in Indonesia. Indonesia had the highest malaria incidence in Southeast Asia. High levels of morbidity and mortality and antimalarial resistance problems encourage the need to find new antimalarial agents, such as red fruit. Red fruit contains many antioxidants and has been reported to have effect of reducing parasitemia. This study aims to determine the effects of red fruit oil on reducing parasitemia in mice infected with Plasmodium berghei. This experimental study with a post-test only control group design used 32 mice as samples and divided it into 8 groups (control group (aquadest); chloroquine group 0.5 mg / grBB, red fruit oil group doses of 0.1 cc, 0.2 cc and 0.4 cc; combination group of red fruit oil doses of 0.1 cc, 0.2 cc and 0.4 cc, with chloroquine 0.5 mg/grBB). Research data was processed using Mann-Whitney test and Kruskal Wallis test because the data didn’t meet one way ANOVA test requirements. The results showed effect of red fruit oil on decreasing parasitemia in mice infected with Plasmodium berghei (p